2002
DOI: 10.1159/000057883
|View full text |Cite
|
Sign up to set email alerts
|

Palmar Erythema: Cutaneous Marker of Neoplasms

Abstract: Background: Acral erythema on the palms is observed in several conditions. However, the relationship with malignant tumors has only been reported exceptionally. It should be noted that tumors produce angiogenic mediators. Objective: These mediators might promote palmar erythema (PE), and the aim of the present study was to investigate the vasodilation of palmar skin capillaries and angiogenesis, mainly with tumors of the central nervous system. Methods: In a prospective study of 107 patients affected by brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Noble et al . found palmar erythema in 27 of 107 brain tumors (25.1%) 23 . In our study, we found palmar erythema at a rate of 0.28% (2 of 700 cases).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Noble et al . found palmar erythema in 27 of 107 brain tumors (25.1%) 23 . In our study, we found palmar erythema at a rate of 0.28% (2 of 700 cases).…”
Section: Discussionsupporting
confidence: 59%
“…found palmar erythema in 27 of 107 brain tumors (25.1%). 23 In our study, we found palmar erythema at a rate of 0.28% (2 of 700 cases). Contrary to these reports we found palmar erythema in two patients with breast cancer.…”
Section: Discussionsupporting
confidence: 49%
“…Because it occurred in patients after beginning cytotoxic chemotherapy, with rapid improvement upon discontinuing therapy, it was believed to be a side effect associated with various cytostatic agents [2]. Nevertheless, there were isolated reports of clinical appearances similar to chemotherapy‐associated HFS in patients with neoplasia [3, 4] or graft‐versus‐host disease [5]. HFS is characterized by painful erythematous lesions which mainly affect palmoplantar surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 In a clinicopathologic study of brain tumors, palmar erythema was recognized in 27 (25%) of 107 patients. 5 Histologic examination in that study demonstrated that the intensity of erythema correlated with both cutaneous vessel dilation and prominent vascularization in the patients' brain tumors, suggesting the role of circulating angiogenic factors such as VEGF. VEGF is a potent mediator of angiogenesis, which is critical for tumor development and growth.…”
Section: Conditions In the Differential Diagnosismentioning
confidence: 99%